Typology of Fisheries Sector and Income Disparities at Cirebon Regency - Achmad Rizal; Iwang Gumilar; Lupita Lestari (Jurnal Perikanan dan Kelautan, 2017)
Development is directedactions to obtain a better quality of life. Development policy is intended to provide equity in the part of development, but the disparities between regions are still occur. The actual disparities are caused by potential distinct of Natural Resources (SDA) and demographic conditions which in the development process lead to uneven distribution of income per capita. This study aims to analyze the major disparities of coastal and non-coastal income in Cirebon Regency and analyze the position of the fishery sector as the economic base in Cirebon Regency in year 2011-2015. This research was conducted by survey method, the sampling technique by purposive sampling method. Data collection technique by recording directly on time series data sheets from 2011-2015 and filling questionnaires by coastal and non-coastal communities, the Department of Marine and Fisheries, Planning Agency Regional Development, as well as the Central Bureau of Statistics of Cirebon Regency. The results showed that income disparities in non-coastal areas were higher than coastal areas with an average value of the Williamson Index of 0.20 for coastal areas and 0.29 for non-coastal areas, while through economic base analysis showed that fishery sub-sector in Kabupaten Cirebon is the economic base sector with some superior commodities such as tiger shrimp, shellfish, octopus and crab.